Canine Tooth Position and its Relationship with the Perpendicular Line to the Nasal Ala in an Iranian Population - Zahedi, Zeinab; Shayegh, Sayed Shojaedin; Sherafatmand, Yasaman; Bafandeh, Mohammad Amin (Galen Medical Journal, 2024)
Background: Position of anterior teeth is an important step in smile design and fabrication of full dentures. This study aimed to assess the canine tooth position and its relationship with the line drawn perpendicular to the nasal ala in an Iranian population. Materials and Method: This analytical epidemiological field study was conducted on 100 males and 100 females presenting to the dental clinic of Shahed Dental School in June 2023. Digital photographs were obtained from the patients under standardized conditions. Reference lines were drawn perpendicular to the nasal alae and continued down to the lower lip (AI lines). The distance from the canine cusp tip (AICT) and distal contact point of the canine tooth (AICD) to the AI line was measured bilaterally using Digimizer software version 6. Data were analyzed by t-test (alpha=0.05). Results: The AICT and AICD were significantly larger than zero in both males and females (P<0.05). The mean AICT and AICD in males were larger than those in females by 2-2.5 mm. No significant difference was found in the right and left canine position, neither in males nor in females (P>0.05). Conclusion: According to the results, the AI line and gender both affected the canine position in the study population, and therefore, should be taken into account in designing an esthetically pleasant denture. Canine position properly determined for one side may be used for the other side as well since no significant difference was found in the right and left canine position.